The role of bank finance in small firm growth : a case study - Musengi, Sandra (Rhodes University, Faculty of Commerce, Department of Management, 2003)
The debate concerning small firm access to finance continues. The proliferation of research of the issue underlines the importance attached in promoting a strong entrepreneurial culture within a country. Small firms are significant to economic growth if they are growing. Central to this significance is ascertaining the role of finance and in particular bank finance in accelerating small growth potential. The case study, through its ontological, epistemological and methodological position, draws on a document review and interview material from small firm owners and key informants to explore the role of bank finance in small firm growth. Case study evidence reveals that small firm owners do not intend to finance firm growth with bank finance but prefer to finance growth with internally generated funds. The owners indicate that non-financial and behavioural factors, such as, maintaining decision-making control, experience accessing bank finance, the perception of the banking relationship and growth aspirations of owners may be more important in dertermining the finance structure for firm growth. From the bank's perspective, findings suggest that risk assessment, financial viability of the enterprise and provision of collateral are more important in the lending decisions; findings supported by an analysis of selected documents. The small sample of small firm owners, bank representatives, experts and documents makes it difficult to generalize the findings. However, the findings are significant because exploring the issue from different perspectives presents invaluable insights, which can be investigated further to assist small firm owners, to develop finance products geared for small firm operations, and in the development of the knowledge base on finance-related issues in the South African context.
Keywords: Banks and banking -- South Africa; Finance -- South Africa; Small business -- South Africa -- Finance; Small business -- South Africa -- Growth -- Case studies; Entrepreneurship -- South Africa; New business enterprises -- South Africa; Bank loans -- South Africa